Patients with primary varicose veins have few venous valves in the proximal femoral vein and great saphenous vein: A cadaveric and ultrasound examination of living subjects. - Mitsuoka, Hiroki; Yodogawa, Chihiro; Arima, Takahiro; Wanibuchi, Sora; Naito, Munekazu; Kodama, Akio (Phlebology, 2026)
Objectives: The pathogenesis of primary varicose veins (PVVs) is multifactorial and remains incompletely understood; however, venous valve dysfunction is recognized as a key factor. Previous studies have suggested racial differences in the prevalence and distribution of venous valves in the proximal femoral vein; however, no data are available for the Japanese population. This study aimed to clarify the prevalence and number of venous valves in the proximal femoral vein and great saphenous vein (GSV) in Japanese individuals and determine whether patients with PVVs have fewer venous valves than healthy individuals. Methods: A cadaveric study of 59 individuals (median age, 87 years) and an ultrasound study involving 52 healthy volunteers (median age, 26 years) and 106 patients with PVVs (median age, 72 years) were conducted. Venous valves were assessed in segments A (from the confluence of the inferior epigastric vein to the saphenofemoral junction [SFJ]) and B (GSV within 4 cm distal to the SFJ). Results: In cadavers and volunteers, venous valves were identified in approximately 60% of segment A and nearly all of segment B, with no significant differences between the two groups. Conversely, patients with PVVs had significantly fewer venous valves in both segments A (right, 0.22 vs 0.54, p <.001; left, 0.31 vs 0.56, p =.005) and B (right, 1.29 vs 1.50, p =.034; left, 1.32 vs 1.52, p =.028) than volunteers. In several PVVs, only the venous sinus without valve leaflets was detectable by ultrasonography. Conclusions: Patients with PVVs had significantly fewer venous valves in the proximal femoral vein and GSV than healthy subjects, suggesting that valve deficiency, possibly including congenital factors, may contribute to PVV development. This study provides the first detailed data on venous valve distribution in Japanese individuals. More studies are needed to confirm these findings and clarify clinical implications.